STRATIFIED RANDOMIZED RESPONSE MODELS: AN APPLICATION TO STUDENTS OF THE FACULTY OF MATHEMATICS OF THE UNMSM - Solano Dávíla, Olga (2010)
In the present work, we study three stratified randomized response models, used in surveys that involve sensitive question (Kim and Elam, 2003). Made an application in the behavior of youths from the Faculty of Mathematical Sciences of San Marcos, to investigate the proportion of people who have consumed cocaine basic paste (CPB) at least once in life and the proportion of current users of the CPB and the proportion of people who had sex with more than two people for life and the proportion of people who consuming alcohol every weekend and the proportion of people who have been or are consumed without paying any products from a supermarket. The populations in study were students matriculated in the half-yearly 2009 - 11.